Peran agency cost reduction dalam memediasi hubungan antara corporate social responsibility dengan nilai perusahaan - Alfini Maryanti Liu; Irwansyah Irwansyah; Zaki Fakhroni (Faculty of Economics and Business Mulawarman University, 2016)
The purpose of this study was to analyzed the effect of CSR on firm value. Firm value proxy with Tobin’s Q. This research was taken because there are still differences between the researchs with each other. This research adding agency cost reduction as mediating variable. This research was not use stakeholder theory, but was applicated agency theory, signaling theory, and legitimacy theory. This study use WarpPLS 5.0. This study uses 63 samples of manufacture firms that listed in Indonesian Stock Exchange (IDX) during 2013 to 2015. The sampling method used for this study is purposive sampling. Type of the data used is secondary data. The result of the test is that CSR positive influence to the firm value. Based on the results of the analysis found that the agency cost reduction is partial mediation between the relationship of CSR on firm value. Institutional ownership can’t moderate CSR on ACR.Keyword: Corporate Social Responsibility, Firm Value, Agency Cost Reduction, Institutional Ownership